The Teacher/ Researcher and the Role of Pre-understanding: A Personal Analysis - Thomas G. Ryan (New Zealand Journal of Teachers' Work)
The acknowledgement of pre-understanding is imperative within research and/or teaching. Pre-understanding consists of both explicit and tacit knowledge that can best be understood as two levels or planes; namely, firsthand and second-hand pre-understanding. First-hand pre-understanding, acquired through personal experience, is distinct from second-hand which is collected through the pre-understanding of other people (intermediaries). Preunderstanding includes knowledge within a certain disposition which surfaces while collecting, analyzing and processing information within one’s role as teacher and/or researcher. To fully comprehend pre-understanding, three distinct elements including membership (teaching fraternity), experience, and education and training are explored using personal experiences.